Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Terhadap Kecerdasan Interpersonal Siswa Dalam Mata Pelajaran PAI Di Kelas XI SMAS Asshiddiqiyah - Maria, Anly; NURWANTI, GITA (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Interpersonal Intelligence is an individual's ability and skill to create, build, and maintain social relationships. In the context of Islamic Religious Education (PAI) courses, students' interpersonal intelligence has not yet developed adequately. This is evidenced by instances where students exhibit a lack of mutual respect for others' opinions during the learning process, passive participation, hesitation to express their views in front of others, shyness, predominance of more capable students during the learning process, lack of cooperation among group members, and insufficient stimuli encouraging students to express their opinions. The Group Investigation type of cooperative learning model involves students throughout the learning process, which can significantly enhance their interpersonal intelligence. This study aims to describe: (1) the profile of students' interpersonal intelligence in Islamic Religious Education (PAI) learning, (2) the application of the Group Investigation cooperative learning model in PAI courses for the 11th-grade students at SMAS Asshiddiqiyah, and (3) the effect of the Group Investigation cooperative learning model on the interpersonal intelligence of students in PAI courses for the 11th-grade students at SMAS Asshiddiqiyah. This research employs a descriptive correlational quantitative method. Data collection techniques include observation, questionnaires distributed to 23 respondents, interviews, and documentation studies. Data processing was conducted through statistical data analysis. The findings indicate that the application of the Group Investigation cooperative learning model scored an average of 4.30, which falls within the 4.01-5.00 interval, categorized as very good. Additionally, the improvement in students' interpersonal intelligence in PAI courses scored an average of 4.14 and 4.30, both falling within the 4.01-5.00 interval, also categorized as very good. Statistical tests reveal that the implementation of the Group Investigation cooperative learning model accounts for 65.61% of the improvement in students' interpersonal intelligence, aligning with the functions and objectives of Islamic Religious Education, while 34.39% is influenced by other factors not included in this study. Keywords: Cooperative Learning Model, Group Investigation Type, Interpersonal Intelligence, Islamic Religious Education.